Relationship between Education, Sex, and Age with Refractive Errors at DR. Wahidin Soedirohusodo General Hospital - Kadek Dwipa Dyatmika; Nurmawanti Nurmawanti; Rini Kusumawar Dhany (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2019)
The prevalence of refractive error and its relationship with education, age and sex at DR. Wahidin Soedirohusodo general hospital have not been comprehensively assessed. The aim of this study was to examined the distribution and risk factor of refractive errors at DR. Wahidin Soedirohusodo general hospital. Methods of this study used population based cross-sectional study. Respondents were interviewed and underwent standardised clinical eye examinations. Refractive error was determined by an automatic refraction device. Refractive errors are myopia, hyperopia and astigmatism. Myopia and hyperopia were defined as spherical equivalent of -0.50/+0.50 diopter (D) or worse, respectively; astigmatism was defined as cylindrical error >0.50 D. Total of 1760 patients with refractive error from January 2016 to January 2018 with 700 or 39,8% males and 1060 or 60.2% females. Based on the cross-tabulation output, it is known that the respondents with the most elementary level of education experienced mild hypermetropy (10.2%), the junior high school education experienced mild myopia (6.8%), high school and bachelor education experienced mild myopia (8%). Age 6-15 years experienced the most myopia compositus astigmatism (5.7%), 16-25 years mild myopia (10.2%), 26-35 years mild myopia (4.5%), 36-45 years mild myopia (10.2%), 46-55 years mild hypermetropia (10.2%) and 56-65 years mild hypermetropia (5.7%). Kruskal Wallis test it is known that the sig value obtained = 0,000 indicates that there are differences in refractive abnormalities based on education and age. Chi square sig value obtained is 0.021, indicating that there is a relationship between sex and refractive errors. Multivariate analysis revealed female subjects inhibited the risk of mild myopic by 0.157 times the male subjects and simple myopia astigmatism by 0.082 times the male subjects. The relationship of myopia, astigmatism and hypermetropia with age and education is not significant. The risk factor of mild myopia and simple myopia astigmatism decrease in female than male. These findings may help clinicians to better understand the patterns of refractive error and planning for preschool vision-screening programs.